Original paperPolish statement on food allergy in children and adolescents - Kaczmarski, Maciej; Wasilewska, Jolanta; Jarocka-Cyrta, Elżbieta; Cudowska, Beata; Żur, Elżbieta; Matuszewska, Elżbieta; Stańczyk-Przyłuska, Anna; Zeman, Krzysztof; Kamer, Barbara; Korotkiewicz-Kaczmarska, Elżbieta; Czaja-Bulsa, Grażyna; Czerwionka-Szaflarska, Mieczysława; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
An adverse food reaction is defined as clinical symptoms occurring in children, adolescents or adults after ingestion of a food or chemical food additives. This reaction does not occur in healthy subjects. In certain individuals is a manifestation of the body hypersensitivity, i.e. qualitatively altered response to the consumed food. The disease symptoms observed after ingestion of the food can be triggered by two pathogenetic mechanisms; this allows adverse food reactions to be divided into allergic and non-allergic food hypersensitivity (food intolerance). Food allergy is defined as an abnormal immune response to ingested food (humoral, cellular or mixed). Non-immunological mechanisms (metabolic, pharmacological, microbiological or other) are responsible for clinical symptoms after food ingestion which occur in non-allergic hypersensitivity (food intolerance). Food allergy is considered a serious health problem in modern society. The prevalence of this disorder is varied and depends, among other factors, on the study population, its age, dietary habits, ethnic differences, and the degree of economic development of a given country. It is estimated that food allergy occurs most often among the youngest children (about 6-8% in infancy); the prevalence is lower among adolescents (approximately 3-4%) and adults (about 1-3%). The most common, age-dependent cause of hypersensitivity, expressed as sensitization or allergic disease (food allergy), are food allergens (trophoallergens). These are glycoproteins of animal or plant origine contained in: cow’s milk, chicken egg, soybean, cereals, meat and fish, nuts, fruits, vegetables, molluscs, shellfish and other food products. Some of these allergens can cause cross-reactions, occurring as a result of concurrent hypersensitivity to food, inhaled or contact allergens. The development of an allergic process is a consequence of adverse health effects on the human body of different factors: genetic, environmental and supportive. In people predisposed (genetically) to atopy or allergy, the development of food allergy is determined by four allergic-immunological mechanisms, which were classified and described by Gell-Coombs. It is estimated that in approximately 48-50% of patients, allergic symptoms are caused only by type I reaction, the IgEmediated (immediate) mechanism. In the remaining patients, symptoms of food hypersensitivity are the result of other pathogenetic mechanisms, non-IgE mediated (delayed, late) or mixed (IgE mediated, non-IgE mediated). Clinical symptomatology of food allergy varies individually and depends on the type of food induced pathogenetic mechanism responsible for their occurrence. They relate to the organ or system in which the allergic reaction has occurred (the effector organ). Most commonly the symptoms involve many systems (gastrointestinal tract, skin, respiratory system, other organs), and approximately 10% of patients have isolated symptoms. The time of symptoms onset after eating the causative food is varied and determined by the pathogenetic mechanism of the allergic immune reaction (immediate, delayed or late symptoms). In the youngest patients, the main cause of food reactions is allergy to cow’s milk. In developmental age, the clinical picture of food allergy can change, as reflected in the so-called allergic march, which is the result of anatomical and functional maturation of the effector organs, affected by various harmful allergens (ingested, inhaled, contact allergens and allergic cross-reactions). The diagnosis of food allergy is a complex, long-term and time-consuming process, involving analysis of the allergic history (personal and in the family), a thorough evaluation of clinical signs, as well as correctly planned allergic and immune tests. The underlying cause of diagnostic difficulties in food allergy is the lack of a single universal laboratory test to identify both IgE-mediated and non-IgE mediated as well as mixed pathogenetic mechanisms of allergic reactions triggered by harmful food allergens. In food allergy diagnostics is only possible to identify an IgE-mediated allergic process (skin prick tests with food allergens, levels of specific IgE antibodies to food allergens). This allows one to confirm the diagnosis in patients whose symptoms are triggered in this pathogenetic mechanism (about 50% of patients). The method allowing one to conclude on the presence or absence of food hypersensitivity and its cause is a food challenge test (open, blinded, placebo -controlled). The occurrence of clinical symptoms after the administration of food allergen confirms the cause of food allergy (positive test) whereas the time elapsing between the triggering dose ingestion and the occurrence of clinical symptoms indicate the pathogenetic mechanisms of food allergy (immediate, delayed, late). The mainstay of causal treatment is temporary removal of harmful food from the patient’s diet, with the introduction of substitute ingredients with the nutritional value equivalent to the eliminated food. The duration of dietary treatment should be determined individually, and the measures of the effectiveness of the therapeutic elimination diet should include the absence or relief of allergic symptoms as well as normal physical and psychomotor development of the treated child. A variant alternative for dietary treatment of food allergy is specific induction of food tolerance by intended contact of the patient with the native or thermally processed harmful allergen (oral immunotherapy). This method has been used in the treatment of IgE-mediated allergy (to cow’s milk protein, egg protein, peanut allergens). The obtained effect of tolerance is usually temporary. In order to avoid unnecessary prolongation of treatment in a child treated with an elimination diet, it is recommended to perform a food challenge test at least once a year. This test allows one to assess the body’s current ability to acquire immune or clinical tolerance. A negative result of the test makes it possible to return to a normal diet, whereas a positive test is an indication for continued dietary treatment (persistent food allergy). Approximately 80% of children diagnosed with food allergy in infancy “grow out” of the disease before the age of 4-5 years. In children with non-IgE mediated food allergy the acquisition of food tolerance is faster and occurs in a higher percentage of treated patients compared to children with IgE-mediated food allergy. Pharmacological treatment is a necessary adjunct to dietary treatment in food allergy. It is used to control the rapidly increasing allergic symptoms (temporarily) or to achieve remission and to prevent relapses (long-term treatment). Preventive measures (primary prevention of allergies) are recommended for children born in a “high risk” group for the disease. These are comprehensive measures aimed at preventing sensitization of the body (an appropriate way of feeding the child, avoiding exposure to some allergens and adverse environmental factors). First of all, the infants should be breast-fed during the first 4-6 months of life, and solid foods (non milk products, including those containing gluten) should be introduced no earlier than 4 months of age, but no later than 6 months of age. An elimination diet is not recommended for pregnant women (prevention of intrauterine sensitization of the fetus and unborn child). The merits of introducing an elimination diet in mothers of exclusively breast-fed infants, when the child responds with allergic symptoms to the specific diet of the mother, are disputable. Secondary prevention focuses on preventing the recurrence of already diagnosed allergic disease; tertiary prevention is the fight against organ disability resulting from the chronicity and recurrences of an allergic disease process. Food allergy can adversely affect the physical development and the psycho-emotional condition of a sick child, and significantly interfere with his social contacts with peers. A long-term disease process, recurrence of clinical symptoms, and difficult course of elimination diet therapy are factors that impair the quality of life of a sick child and his family. The economic costs generated by food allergies affect both the patient’s family budget (in the household), and the overall financial resources allocated to health care (at the state level). The adverse socio-economic effects of food allergy can be reduced by educational activities in the patient’s environment and dissemination of knowledge about the disease in the society.